Determination of Johnson–Cook Material and Failure Model Constants for High-Tensile-Strength Tendon Steel in Post-Tensioned Concrete Members - Ioannis Gkolfinopoulos; Nobuhiro Chijiwa (Applied Sciences, 2022)
The estimation of damage in steel tendons is important for evaluating the remaining capacity of existing tensioned members. This research focuses on calculating Johnson–Cook (LC) model and damage parameters of high-strength steel material through quasi-static and dynamic uniaxial tests. Finite element analysis is used to replicate the experimental procedure, and through dynamic image correlation analysis, the numerical results accuracy is verified. In this investigation, it is found that the JC model can accurately replicate deformation and stress concentration under different strain rates and triaxiality conditions and, thus, can be used for fracture analysis of prestressed concrete members.